Dante's visions
1 online resource.
Keywords: "Dante's Visions: Crossing Sights on Natural Philosophy, Theory of Vision, and Medicine in the Divine Comedy and Beyond offers a fascinating insight into Dante's engagement with the science of his time, particularly with visual perception and neurological disorders. The connection between soul and body and between human beings and their natural environment were relevant fields of interest in the medieval world. In Dante's Divine Comedy, as well as in his Vita Nuova and Convivio, these connections are enhanced to the fullest, expressing feelings and sensations, pain and ecstasy, physical and spiritual passions under exceptional psychological and environmental stimuli. Based on the research of a multidisciplinary group of scholars - including experts in Dante, the culture and history of medieval literature and philosophy, historians of science, neuroscientists, and specialists in vision and visual illusions - this book explores the poet's psychophysical descriptions of sense perception, the theory of vision, optical illusions and deceptions of sight, neurological phenomena, and the anatomy and physiology of the human nervous system. It highlights the Aristotelian sources of his scientific culture and the influence of the Arabic sciences on their dissemination in the Western world. In addition to illustrating the cultural background of a poetic genius, with specific reference to the rich scientific reflections in Italy at Dante's time, the book brings out the many opportunities for future research at the intersection of science and literature in the past"--